Mixed Messages: I. The Consequences of Communicating Negative Statements Within Emotional Support Messages to Cancer Patients. (August 2020) - Ray, Colter D; Floyd, Kory; Tietsort, Cris J; Veluscek, Alaina M; Otmar, Christopher D; Hashi, Emi C; Fisher, Rosalie
Background: Not all emotional support messages consist purely of positive statements. Some emotional support messages received by cancer patients simultaneously communicate statements of caring but also negative statements, such as criticisms of patients' actions. Objective: This study tests if a negative statement occurring within an emotional support message affects cancer patients' perceptions of the effectiveness of the entire emotional support message as well as the perceived competence of the supporter communicating the emotional support message. Methods: Cancer patients watched video recordings of emotional support messages and subsequently provided ratings on message effectiveness and supporter competence. Some emotional support messages included negative statements, whereas other messages did not. Results: Messages that included a negative statement were rated lower on message effectiveness than messages without negative statements. Cancer patients rated supporters communicating messages with a negative statement as having significantly less competence than those who did not communicate a negative statement. Conclusion: A single negative statement occurring within an emotional support message may result in cancer patients viewing the emotional support as less effective and the supporter as less competent.